How To Do Critical Appraisal of Any Research Article - Prasad, Rachana; Mallick, Kallol; Gaurav, Abhishek; Prasad, Rajiv; Mazumdar, Anamika (National Journal of Community Medicine, 2022)
In both biomedical research and medical academia, research publications serve a critical role. There are a huge number of research publications published all around the world. However, only a small percentage of them are good and have any research or academic worth. So, properly evaluating published publications has become vital in this circumstance. This article is intended with medical graduates and postgraduates in mind, in order to clarify them how to critically evaluate research publications. It may also be used to write published research articles in an indirect way. A collection of questions is supplied to cover all aspects of a published research paper. To assess the quality of an article, a score system based on the following questions can be established.